2012
DOI: 10.1111/j.1468-3083.2012.04646.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary intention healing in skin surgery: our own experience and expanded indications in hidradenitis suppurativa, rhinophyma and non‐melanoma skin cancers

Abstract: SIH is a safe and efficient form of treatment for various post-operative skin defects. In certain areas of the body, SIH shows favourable cosmetic and functional effects. In these cases, it may even be regarded as the method of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Previously, Bieniek et al 15 demonstrated favourable cosmetic results of secondary intention healing after HS surgery. We argue that secondary intention healing prevents recurrences because there will be no entrapment of epithelial strands or debris, as can occur after primary closure.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, Bieniek et al 15 demonstrated favourable cosmetic results of secondary intention healing after HS surgery. We argue that secondary intention healing prevents recurrences because there will be no entrapment of epithelial strands or debris, as can occur after primary closure.…”
Section: Discussionmentioning
confidence: 97%
“…The width of the excision and not the wound closure technique influenced the therapeutic outcome [25, 27, 29], whereas vacuum-assisted closure may accelerate the time-point of a delayed primary closure as shown by a retrospective study [30]. On the other hand, secondary intention healing revealed “good’ or “excellent” results in 27.3 % and 39.4 %, respectively, of 97 cases studied after 12 months of follow-up [31]. Buimer et al [24] observed 41 % recurrences in 200 patients treated with radical surgery and closed by primary closure or skin graft.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with extensive disease at multiple locations are usually operated in several sessions. The wounds are allowed to heal by secondary intention as in our experience, and that of others, it is time‐efficient and leads to good cosmetic and functional results . Furthermore, it allows prolonged wound drainage, diminishing the risk of wound infection …”
Section: Discussionmentioning
confidence: 80%